FOREIGN LANGUAGE ANXIETY EXPERIENCES OF FILIPINO STUDENTS ACROSS THE FOUR MACRO SKILLS - Gianinna Elaine Malapote Labicane (Universitas Islam Sumatera Utara (UISU), 2021)
Throughout the years, scholars have determined that foreign language learning is associated with negative emotional reactions rooted from communication apprehension, test anxiety, and fear of negative evaluation; a phenomenon more widely known as Foreign Language Anxiety (FLA), which has effectively hindered language learning for many students. Moreover, it does not help that the abrupt and drastic pedagogical transformations brought about by the COVID-19 pandemic in itself has proven to be stressful and anxiety-provoking for the learners. In this context, the aim of this study was to determine the foreign language anxiety experienced by Filipino learners in the remote learning setup. This mixed method study gathered data from 83 Filipino college students about their FLA experience across the four macro skills: reading, writing, listening and speaking amidst remote learning. Results revealed the participants experienced the highest level of anxiety with speaking. However, it must be noted that the fear of making mistakes and fear of negative evaluation can be observed across all the four macro-skills. Participants also struggle with opportunities to improve across the four macro skills due to the intermittent internet connection, inadequate resources, and limited interaction with their teachers and peers.